Tax Rates and Tax Evasion: Evidence from “Missing Imports” in China - Fisman, Raymond; Wei, Shang‐Jin (Journal of Political Economy, 2004)
Tax evasion, by its very nature, is difficult to observe. We quantify the effects of tax rates on tax evasion by examining the relationship in China between the tariff schedule and the "evasion gap," which we define as the difference between Hong Kong's reported exports to China at the product level and China's reported imports from Hong Kong. Our results imply that a one-percentage-point increase in the tax rate is associated with a 3 percent increase in evasion. Furthermore, the evasion gap is negatively correlated with tax rates on closely related products, suggesting that evasion takes place partly through misclassification of imports from higher-taxed categories to lower-taxed ones, in addition to underreporting the value of imports.